Snatched from Earth! - "Coville, Bruce" (Hodder Children's books: London, 2000)
Imagine if the first alien kid to land on Earth was sent to your school - not in secret, but with the kind of open fanfare of Chelsea Clinton going to Stanford or Prince Harry attending Eton. That's what happened at Tim Tompkins' school...
Keywords: Human-alien encounters